Sharia Economic Law Perspective On Productive Zakat Management During The Covid 19 Pandemic Case Study Of The National Zakat Amil Agency (Baznas) - Pertiwi, Hardianti (Jurnal Ar-Ribh, 2022)
The arrangement of zakat must involve aspects of reliable modern management, so that zakat becomes a meaningful force. The arrangement includes aspects of data collection, collection, storage and distribution, during the covid 19 pandemic, of course many problems arise, one of which is Productive Zakat Management, where this study aims to determine whether BAZNAS Masamba, North Luwu Regency, South Sulawesi Province carries out administrative management in The Covid 19 pandemic period is in accordance with the Sharia Economic Law Perspective, so that the goal of improving the Mustahiq's Economy is going well. The type of research used is qualitative with a case study approach and empirical normative research, namely legal research regarding the direct application of normative provisions to every legal event that occurs in society. In the results of research related to the Management of Productive Zakat Management during the Covid 19 Pandemic, it is in accordance with Sharia Economic Law and Law. Number 23 of 2011, however, in the management of productive zakat where the Human Resources factor is still being worked out because the mentoring process for Mustahiq has not been well optimized and the socialization of zakat has not been thoroughly informed, thus the community does not understand the management and benefits of productive zakat.